Assemblages of Living Together: Residential Cohabitation in Peri-urban Areas of Chengdu and Hyderabad - Liubing Xie (South Asia Multidisciplinary Academic Journal)
At a time when China and India are urbanizing rapidly, the transformation of the urban peripheries has brought into close proximity social groups who previously had little or no contact with each other. In this article, I approach the question of residential cohabitation by investigating similar types of residential areas in Chengdu and Hyderabad, which are emblematic of those found in the urban peripheries: autoconstructed communities and gated communities. Inspired by research on urban assemblages, and on the basis of fieldwork conducted in each setting, I introduce the notion of “assemblages of living together.” I have identified three key assemblages associated with three distinct forms of residential cohabitation: the interspersion of autoconstructed communities and gated communities, heterogeneity within the same residential communities, and vertical cohabitation of villager landlords and migrant tenants. Between and within the various assemblages of living together, I have observed two main types of relationalities between residents: different social groups are physically proximate but socialize separately according to certain norms that often materialize as physical boundaries such as walls, roads, and different floors of the building; at times interdependence between different social groups emerges, but it is based on unequal interactions.